PENYULUHAN DAN PERUBAHAN PENGETAHUAN CUCI TANGAN PAKAI SABUN DI DESA SUKOWIDI KABUPATEN MAGETAN - Avicena Sakufa Marsanti (Jurnal Kesehatan Manarang, 2017)
Data from primary health care Panekan showed that incidence of diarrhea was increased. The Cause of Diarrhea is a wrong Hand washing Practice. Based on interview over the last 6 month, 10 people didn’t know the importance of hand washing. The objective of this study was to determine This study was experimental one group pretest and postest design with 100 family for samples and proportionate random sampling technique. This study was analyzed by paired t-test with significance P>0.05. The result showed that there was an effect between counseling and knowledge about hand washing with soap (p<0,001). Before the counseling, the mean of knowledge score was 63,6±7,91 and after counseling was 79,90±7,25. There was an effect of counseling and changes in knowledge about hand washing with soap in Sukowidi, Magetan, the mean of knowledge score was better after counseling.